(untitled) (Physical Education, Health and Social Sciences, 2025)
Objective: The COVID-19 pandemic has precipitated a global mental health crisis. This study aimed to investigate the prevalence of COVID-19-related stress and its psychological impact (anxiety and depression) on the residents of Karachi, Pakistan. Methods: A cross-sectional study was conducted over six months (February to July 2021). Data were collected from 306 COVID-19 patients admitted to Jinnah Postgraduate Medical Centre (JPMC), Karachi, using a structured questionnaire. The instrument measured stress (20 items) and psychological impact (9 items) on a 5-point Likert scale. Data were analyzed using Principal Component Analysis (PCA) and Linear Regression in SPSS version 16. Results: The sample had a mean age of 34.12±8.57 years, was predominantly male (88.2%), married (82.4%), and employed (90.2%). PCA revealed that items related to anger (S12), fear of infecting family (S16), and depressed mood (S19) induced the highest stress. For psychological impact, the fear for family members’ health (P4) was the most severe. Regression analysis showed a strong, significant relationship between COVID-19 stress and psychological impact (R = 0.855, R² = 0.731, p < .001). Conclusion: The study concludes that the COVID-19 pandemic has inflicted severe psychological distress, including high levels of stress, anxiety, and depression, on the population of Karachi. These findings underscore an urgent need for public health interventions aimed at mitigating the mental health repercussions of the pandemic through targeted support systems and psychological first aid.